THE EFFECT OF ONLINE AND OFFLINE LEARNING METHODS ON THE PSYCHOLOGICAL IMPACT OF STUDENTS - Asri Bashir; Nurlela Mufida (Universitas Respati Yogyakarta, 2022)
The Covid-19 pandemic that hit the world, Indonesia and Aceh Province has impacted various sectors. Not only the economic sector, the teaching and learning process is also disrupted. The teaching and learning process cannot be done face-to-face, to prevent the spread of the corona virus. Anticipating the transmission of the virus, the government has issued various policies, such as isolation, social and physical distancing to large-scale social restrictions (PSBB). The purpose of the study was to identify whether the influence of online and offline learning models on the psychological impact of STIKes Medika Nurul Islam students. The type of research used is quantitative with a one-sample quasi-experimental design. The number of respondents in this study amounted to 160 students with sampling techniques using random sampling techniques. In this study researchers assessed the psychological impact of students with 3 aspects, anxiety, stress and depression using a watershed questionnaire. The results of this study showed there was an influence of online and offline learning on the psychological impact of students with a value of < 0.05. student anxiety was obtained p value 0.010, student stress was obtained p value 0.023, and student depression was obtained p value 0.001. From the results of this study that there is an influence of online and offline learning methods on the psychological impact of students. Keywords: Learning; Online; Offline; Psychological Impact; Student